Diferencias morfométricas de dos especies del género Eatoniella en Isla Navarino, Reserva de Biosfera Cabo de Hornos, Chile - Rosenfeld, Sebastián; Aldea, Cristian; Ojeda, Jaime; Mansilla, Andrés; Rozzi, Ricardo (Revista de Biología Marina y Oceanografía, 2019)
The external morphometrics of shell and radula morphology were performed in two species of micromollusks of the genus Eatoniella in Navarino Island, Chile. A total of 50 specimens of E. picea and 72 of E. nigra were analyzed. These species have similar morphology, but E. picea has a smaller diameter/length ratio (0.53 ± 0.02) than E. nigra (0.61 ± 0.04). In relation to the radula morphology, E. picea has wider middle cuspid teeth and small denticles in its border, meanwhile E. nigra has pointed central cuspid teeth.